CASE STUDY OF CONSTRUCTED A PROSPEROUS FOOD RESTAURANT BASE ON INNOVATIVE BUSINESS MODEL - Lu, Te-Tsai; Shen, Shu-Fen (International Journal of Application on Economics and Business, 2023)
The aim of this study is to propose a new term "prosperous food (盛食)" instead of "surplus food (剩食)", in order to change the concept of consumers. Since the term “surplus” imply a negative image while the term “prosperous” owed the positive image. This can reduce the wasting food in our society and build a new business model. The start-up plan wishes to build a prosperous food restaurant and at this space can sale prosperous food directly and also the food of re-produce prosperous food. This restaurant plays the role to distribute the prosperous of farm products to consumers. Then we also to hold the prosperous food holiday market and recruit consumers to harvest farm product in farm periodically. We hope we can promote this model over Taiwan after we stabilize this model in Tainan first.